Leading for the Long Future. Issue 72 (March 2014) - Goleman, Daniel
Abstract: Leaders with courage and foresight, Goleman contends, make decisions "with the long horizon in mind." This requires consideration of such areas as public health and safety, the environment, and the common good. And the horizon can stretch to a century or even 500 years. "Reinventing business for the long future, " he writes, "could mean finding shared values supported by all stakeholders, from stock owners to employees and customers to communities where a company operates—to generations as yet unborn." On an individual level, Goleman cites Jefferson, Lincoln, Gandhi, Mandela, Buddha, and Jesus as those leaving legacies far into the future.